Understanding the Rising Trend in Female Labour Force Participation - Nicolas Herault; Guyonne Kalb (Institute of Labor Economics (IZA), 2020)
Female labour force participation has increased tremendously since World War II in developed countries. Prior research provides piecemeal evidence identifying some drivers of change but largely fails to present a consistent story. Using a rare combination of data and modelling capacity available in Australia, we develop a new decomposition approach to explain rising female labour force participation since the mid-1990s. The approach allows us to identify, for the first time, the role of tax and transfer policy reforms as well as three other factors that have been shown to matter by earlier studies. These are (i) changes in real wages, (ii) population composition changes, and (iii) changes in labour supply preference parameters. A key result is that –despite the ongoing emphasis of public policy on improved work incentives for women in Australia and elsewhere– changes in financial incentives due to tax and transfer policy reforms have contributed relatively little to achieve these large increases in participation. Instead, the other three factors drive the increased female labour force participation.
Keywords: H31; J22; J31; 330; female labour force participation; employment rate; tax-transfer policy; behavioural microsimulation; decomposition